Geokimia regional Sulawesi bagian Utara percontoh endapan sungai aktif -80 mesh - Suprapto, Sabtanto Joko (Indonesian Journal on Geoscience, 2006)
http://dx.doi.org/10.17014/ijog.vol1no2.20062Geochemical investigation using the analysis method of -80 mesh of active stream sediment samples is one of the early phase exploration especially in fi nding out metallic mineral deposits. These deposits either as outcrop or as being still in subsurface, can be revealed in geochemical output data. Despite for determination of the availability of mineral deposits, elements distribution of stream sediment samples, can be used to determine the initial and last appearance of geological and situated in environmental condition of an area. Northern part of Sulawesi with its complex geologic setting and a metallogenic region is being potential to form metallic deposits, which create some variation and interesting geochemical performances. The regional geochemistry data by means in the form of elements distribution maps represent the basic important information of mineralization indications, which enable for detail follow up investigation. Â  Â